PERANCANGAN KOLOM BETON BERTULANG GEDUNG PRODI KEDOKTERAN UNIVERSITAS BORNEO TARAKAN DENGAN SISTEM RANGKA PEMIKUL MOMEN - Hernadi, Ahmad; Alstony, Zikri (Civil Engineering Scientific Journal, 2023)
ABSTRACT: The plan to open a medical study program at the Borneo Tarakan University in 2023, of course, must be accompanied by careful planning of structural components. Building elements will actually be designed using a Special Moment Resisting Frame System (SRPMK). Thus, the building is planned to have a high level of ductility against earthquake loads. One of the most important structural components, namely columns, must be designed using the latest standards, namely SNI 2847-2019. The column must be designed with the Strong Column Weak Beam concept to allow damage to occur to the beam first when the structure's ductility level against earthquake loads has been exceeded. The results of the design of the columns in the building are all using K-300 concrete quality and using BJTS-420 quality reinforcement steel for longitudinal and BJTS-280 for stirrups. Longitudinal reinforcement uses a diameter of 19 mm (screw) and shear reinforcement consists of 6 feet with a diameter of 10 mm (screw).Keywords: Column, Medical Study Program, Longitudinal Reinforcement, Transversal Reinforcement, Special Moment Resisting Frame System.ABSTRAK: Rencana pembukaan prodi kedokteran di Universitas Borneo Tarakan pada tahun 2023, tentunya harus diiringi dengan perencanaan komponen struktur yang matang. Elemen gedung sejatinya akan didesain menggunakan Sistem Rangka Pemikul Momen Khusus (SRPMK). Sehingga, gedung direncanakan memiliki tingkat daktilitas yang tinggi terhadap beban gempa. Salah satu komponen struktur yang paling penting yakni kolom harus didesain dengan menggunakan standar terbaru yaitu SNI 2847-2019. Kolom harus didesain dengan konsep Strong Column Weak Beam untuk memungkinkan kerusakan terjadi pada balok terlebih dahulu saat tingkat daktilitas struktur terhadap beban gempa telah terlampaui. Hasil desain kolom pada gedung seluruhnya menggunakan mutu beton K-300 dan menggunakan baja tulangan mutu BJTS-420 untuk longitudinal dan BJTS-280 untuk sengkang. Tulangan longitudinal menggunakan diameter 19 mm (Ulir) dan tulangan geser terdiri 6 kaki dengan diameter 10 mm (Ulir).Kata kunci: Kolom, Program Studi Kedokteran, Tulangan Longitudinal, Tulangan Geser, Sistem Rangka Pemikul Momen Khusus